Low‐Temperature Transformation of Methane to Methanol on Pd1O4 Single Sites Anchored on the Internal Surface of Microporous Silicate. (26th September 2016) - Huang, Weixin; Zhang, Shiran; Tang, Yu; Li, Yuting; Nguyen, Luan; Li, Yuanyuan; Shan, Junjun; Xiao, Dequan; Gagne, Raphael; Frenkel, Anatoly I.; Tao, Franklin (Feng)
Abstract: Direct conversion of methane to chemical feedstocks such as methanol under mild conditions is a challenging but ideal solution for utilization of methane. Pd1 O4 single‐sites anchored on the internal surface of micropores of a microporous silicate exhibit high selectivity and activity in transforming CH4 to CH3 OH at 50–95 °C in aqueous phase through partial oxidation of CH4 with H2 O2 . The selectivity for methanol production remains at 86.4 %, while the activity for methanol production at 95 °C is about 2.78 molecules per Pd1 O4 site per second when 2.0 wt % CuO is used as a co‐catalyst with the Pd1 O4 @ZSM‐5. Thermodynamic calculations suggest that the reaction toward methanol production is highly favorable compared to formation of a byproduct, methyl peroxide.